THE INFLUENCE OF SERVICE QUALITY AND PRICE ON PURCHASE DECISIONS IN CLOTHING STORES AT PARUNG MARKET - Wawan Supriyatna; Purwanti Purwanti; Agus Sudarsono (International Journal Multidisciplinary Science, 2024)
This study aims to identify the influence of service quality and price on the purchase decisions of clothing at stores in Parung Market, both partially and simultaneously. The research is associative and quantitative, with consumers of Parung Market stores as the subjects. The sample consists of 90 individuals selected using Slovin’s formula. Data collection was done through questionnaires, and the data were analyzed using various tests, such as validity and reliability tests, classical assumption tests, linear regression, correlation coefficient, determination coefficient, and partial and simultaneous hypothesis testing. All analyses were performed using SPSS version 25. The results show that service quality affects purchase decisions, with a positive relationship demonstrated by the regression equation. The correlation coefficient indicates a fairly strong relationship between service quality and purchase decisions. In addition, price has a significant influence on purchase decisions, with a higher correlation coefficient compared to service quality. Simultaneously, both service quality and price together influence purchase decisions. This relationship is strengthened by the high and significant correlation coefficient. The conclusion of this study is that both service quality and price, individually or together, play an important role in influencing consumer purchase decisions at Parung Market.